Post-mortem computed tomography in sudden death by asthma. (May 2020) - Smith, Casey; Matoba, Kotaro; Hyodoh, Hideki; Murakami, Manabu; Saito, Atsuko; Matoba, Tomoko; Okuya, Nahoko; Jin, Shigeki
Highlights: Asthma is a new differential diagnosis for lung hypo-attenuation on computed tomography (CT) scans. There are few other specific post-mortem manifestations of fatal asthma on post-mortem computed tomography and standard autopsy. It is important to utilise information from a patient's history to guide further biochemical and histo-pathological investigations. Abstract: Ground glass attenuation (GGA) of the lungs is a common finding of post-mortem computed tomography (PMCT) that is associated with pulmonary congestion and edema due to cardiac failure during the agonal period, or due to post-mortem hypostasis. However, hypo-attenuation of the lung is an atypical finding of PMCT, and is usually a consequence of hypovolemic states before death or postmortem body posture after death. Previous studies have shown a few differential diagnoses, such as hypothermia, massive hemorrhage, asphyxiation by hanging, and dehydration, for hypo-attenuation of the lung. This report presents the case of a woman who died suddenly because of an asthma attack. Our PMCT analysis demonstrated hypoattenuation of the lung in this case. We suggest fatal asthma as a differential diagnosis for the appearance of hypo-attenuation of lungs on PMCT.